Etika Islam dalam Naskah Petikan Qur'an Katut Adab Padikana Karya H. Hasan Mustapa - Asep Saepuloh; Rosihon Anwar; Dadan Rusmana (Jumantara: Jurnal Manuskrip Nusantara, 2021)
This research is entitled Islamic Ethics in the Petikan Qur'an Katut Adab Padikana by H. Hasan Mustapa, a Sundanese manuscript made in 1920 AD. Good relationship between being and God as well as among fellow beings themselves. The purpose of this research is to reveal the verses that show a good relationship between a being and God as well as between the creatures themselves, and to reveal the metaphoric verses in the manuscript. This research method uses the qualitative methods, which seeks to collect data, process and analyze it qualitatively. While the approach used is the Maudu'i interpretation and semiotic theory. Petikan Qur’an Katut Adab Padikana were printed by the Mendakna Committee in 1937 AD after Hasan Mustapa asked for three years before he died to be copied. There are 115 articles consisting of 57 Surah of 356 paragraphs. Starting from the Surah al-Baqarah, to Al-Nass, the explanation uses the van Ophuysena spelling (1907-1947) and the writing process starts from the left corner, namely the verses of the Qur'an then the right corner of the writing of the verses of the al-Qur'an is in the language Latin, and after that the content of the meaning of the verse is explained by using the Sundanese language so that it is easily understood by the people of the Sundanese area.